Amplitude of the Tidal Harmonic Constituents M2, S2, K1, and O1 in Waters Around the City of Bitung in North Sulawesi - Royke M. Rampengan (Jurnal Ilmiah PLATAX, 2013)
ABSTRACT This study was conducted to describe the amplitude of the tidal harmonic constituents M2, S2, K1, and O1 in waters around the city of Bitung in North Sulawesi. Calculations performed using the admiralty method. Based on calculations, it was found that the average amplitude of M2 is 34.8, S2 is 22.5, K1 is 20.3, and O1 is 11.7. The tidal behaviour in the study area is mixed tide predominant semidiurnal, with average Formzahl number of about 0.6. Keywords : amplitude, tidal, Bitung ABSTRAK Penelitian ini dilakukan untuk menggambarkan amplitudo pasut harmonik M2, S2, K1, dan O1 di perairan sekitar kota Bitung di Sulawesi Utara. Perhitungan dilakukan dengan menggunakan metode admiralty. Berdasarkan hasil perhitungan, diketahui bahwa rata-rata amplitudo M2 adalah 34,8, S2 adalah 22,5, K1 adalah 20,3, dan O1 adalah 11,7. Perilaku pasang surut di daerah penelitian adalah air campuran dominan semidiurnal, dengan rata-rata jumlah Formzahl sekitar 0,6. Kata kunci : amplitudo, pasut, Bitung